(3GdfXQjI GdYGeI aj Mbhb GdOaGY CeGe GdbVGA GdLfGFj (B:s (3OQGSI ebGQfI aj GdbGfhf GdhVYj hGdabg GdESdGej (B/s - (3GdYGOdj, eMehO UGdMs ((3GdEScfOQjI, eUQ (B:s (3OGQ GdacQ GdLGeYj,s, 2005)
(3jTJed Ydi edNU HGddZI GdEfLdjRjI(B.s
(3bGFeI eNJUQGJ (B: (3U(B. 861-862.s
(3cTGaGJ (B: (3U(B. 863-874.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdOaGY Yf GdeJge (B((3ELQGAGJ LfGFjI(B)s -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3bGfhf GdELQGAGJ GdLfGFjIs -- (3eUQs